Penentuan Kadar Kalsium Laktat Menggunakan Metode Kompleksmetri - Yuyun Sri Wahyuni; Azzahrah Yusriyah Nasiroh; Aulia Indah Zhanni (Lembaga Pengembangan Kinerja Dosen, 2025)
Complexometry titration is a titration based on the formation of complex compounds between cations and complex forming substances. Complexometry is the formation of colored complexes by metals using standard solutions. The purpose of this study was to determine the percentage of levels in calcium lactate samples. According to the pharmacopoeia edition VI calcium lactate tablets contain no less than 94.8% and no more than 186%. The results obtained from the determination of calcium lactate levels using the Complexometry titration method obtained a level result of 74.68%